Seizures, Retardation, and Creatine Synthesis Defect - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Two unrelated boys, aged 2 and 5 years, with psychomotor retardation, hyperactive behavior, and epilepsy, associated with a creatine synthesis defect, are reported from Free University Hospital, Amsterdam, The Netherlands.